PENINGKATAN KOMPETENSI GURU SMA KABUPATEN BREBES DALAM MENYUSUN SOAL TKA MATEMATIKA - Lilik Ariyanto; Ernawati Saptaningrum; Dyah Nugrahani; Heni Purwati; Ayesha Islam Shaﬁra; Siti Choiriyah; Revita Dewi Lestari (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2025)
This study aims to improve the competency of senior high school teachers in Brebes Regency in designing Mathematics TKA questions through training and mentoring. The implementation method consisted of 2 offline days for harmonizing perceptions and designing questions, one week of structured tasks for question creation, and one online day for presenting results. A total of 56 senior high school teachers from Brebes Regency participated in the training. The pre-training survey showed that most teachers had limited understanding of designing TKA questions, but after the training, there was a significant improvement, with 53 teachers understanding and 50 teachers highly motivated to design TKA questions. Evaluation results indicated high satisfaction, with 50 teachers very satisfied and 55 teachers finding the material highly relevant. In conclusion, the training was effective in improving teachers' competencies in designing TKA questions, although there were challenges related to the limited time and the training's proximity to the exam schedule